Analisis Psikologi Sastra Tokoh Utama dalam Antologi Cerpen Keris Pengantén Karya I Pande Putu Alit Antara - Budiastuti, Ni Kadek; Nerawati, Ni Gusti Ayu Agung (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
This study aims to: (1) Explain the intrinsic structure of the Keris Pengantén short story anthology, (2) Explain the psychological analysis of the main characters in the Keris Pengantén short story anthology. The data collection techniques in this study used library techniques, interviews and documentation. Data analysis in this study was collected through data reduction, data analysis, and drawing conclusions. The collected data were then analyzed using qualitative descriptive methods. The results of this study explain (1) the structure that builds the Keris Pengantén short story anthology, namely events, plot, characters and characterization, setting, theme and moral. The description of the characters is divided into main characters, subordinate characters and additional characters. The settings used are place setting, time setting, social setting. The theme in these four short stories is love. (2) The psychological analysis of literature on the main characters is divided into three, namely id is psychic energy or basic instincts that exist in humans since birth, ego is a psychological aspect related to the real world, and superego is a personality that has evaluative properties and moral teachings. From the explanation above, it can be concluded that the short story anthology Keris Pengantén is built by complete and strong intrinsic elements, especially in the depiction of characters, plot, setting, and consistent themes about love. In addition, through a literary psychology approach, the main character in this short story reflects the dynamics of human personality through the id, ego, and superego. This proves that the short stories in this anthology are not only rich in literature, but also have psychological depth that can provide a greater understanding of human inner conflict.